2022
DOI: 10.1007/s11356-022-20184-3
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolation of anthropogenic disturbances on hazard elements in PM2.5 in a typical heavy industrial city in northwest China

Abstract: Baoji is a typical heavy industrial city in northwest China. Its air quality is greatly impacted by the emission from the factories. Elements in fine particulate matter (PM 2.5 ) that are greatly emitted from anthropogenic sources could pose diverse health impacts on humans. In this study, an online AMMS-100 atmospheric heavy metal analyzer was used to quantify 30 elements in PM 2.5 under the weak and strong anthropogenic disturbance scenarios before the city lockd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Sulfur, Mn, Ni, and As had HQ values slightly above 1, indicating a small risk of non‐carcinogenic toxicity from inhalation of particles in the measurement campaign period. Zhou et al 40 found no HQ value above 1 in their study of non‐carcinogenic risks due to elements in PM 2.5 collected in the industrial city of Baoji, China. The lower HQ in their study can be explained by the study period coincided with the Covid‐19 pandemic lock down.…”
Section: Resultsmentioning
confidence: 97%
“…Sulfur, Mn, Ni, and As had HQ values slightly above 1, indicating a small risk of non‐carcinogenic toxicity from inhalation of particles in the measurement campaign period. Zhou et al 40 found no HQ value above 1 in their study of non‐carcinogenic risks due to elements in PM 2.5 collected in the industrial city of Baoji, China. The lower HQ in their study can be explained by the study period coincided with the Covid‐19 pandemic lock down.…”
Section: Resultsmentioning
confidence: 97%